1994
DOI: 10.1128/aem.60.11.4186-4188.1994
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of bioenergetic parameters with cell death in Listeria monocytogenes cells exposed to nisin

Abstract: In Listeria monocytogenes, nisin induced ATP efflux, reduced the intracellular ATP concentration within 1 min, and dissipated the proton motive force within 2 min. Efilux accounted for only 20% of the ATP depletion, suggesting that ATP hydrolysis also occurred. ATP efflux depended on nisin concentration and followed saturation kinetics. These results suggest that nisin breaches the membrane permeability barrier in a manner more consistent with pore formation than with a nonspecific detergent-like membrane dest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 23 publications
3
26
0
Order By: Relevance
“…The decrease in intracellular ATP and concomitant increase in extracellular ATP observed when L. monocytogenes cells were treated with nisin indicate that intact ATP is leaking from the cells. These results are similar to the findings of Abee et al (1994a) and Winkowski et al (1994) although the efflux in these studies (× 100%) was much greater than the 40% reported for nisin Z and 20% reported for nisin A. Cells treated with pediocin JD and leuconosin S had less efflux of intact ATP (1·5% and 41·1% of initial levels, respectively) although an almost total depletion of intracellular ATP did occur.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…The decrease in intracellular ATP and concomitant increase in extracellular ATP observed when L. monocytogenes cells were treated with nisin indicate that intact ATP is leaking from the cells. These results are similar to the findings of Abee et al (1994a) and Winkowski et al (1994) although the efflux in these studies (× 100%) was much greater than the 40% reported for nisin Z and 20% reported for nisin A. Cells treated with pediocin JD and leuconosin S had less efflux of intact ATP (1·5% and 41·1% of initial levels, respectively) although an almost total depletion of intracellular ATP did occur.…”
Section: Discussionsupporting
confidence: 67%
“…Such interaction of monomers results in pore formation within the membrane . While either model is consistent with the membrane disruption and loss of PMF observed in bacteriocin-sensitive cells, evidence of saturation kinetics and bacteriocin inhibition mechanisms, such as leakage of intracellular ATP and other large molecules, favour the poration complex model (Winkowski et al 1994;Montville et al 1995). Although it has been shown that bacteriocins dissipate PMF in sensitive cells, other inhibitory effects probably occur which are either a result of PMF dissipation or independent of any effect on PMF.…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations